(3eHGOF GdJShjb GdMOjK (B/s - (3TQaI, McjeIs ((3GdLRGFQ(B: s (3OGQ GdNdOhfjI(B, s, 2019)
(3CSGSjGJ Mhd GdJShjb, JMdjd GdHjFI GdJShjbjI ddeDSSI, HMhK GdJShjb, eY GdGSJQGJjLjI GdJShjbjI, HGdEVGaI Gdi GNJjGQ GdCShGb GdeSJgOaI(B: (3JLRFI GdShb, GdGSJgOGa hGdJehbY, JNWjW GdeRjL GdJShjbj, hYhGed JMOjOgeY OQGSI Sdhc GdeSJgdc hGdYhGed GdfaSjI hGdeDKQGJ GdKbGajI, hCNjQG JcfhdhLjG GdGJUGd hEOGQI GdYdGbI eY GdRHGFf aj Xd GdJShjb GdGdcJQhfj(B.s
(3eQGLY U(B.190s
Keywords: (3GdJShjbs; (3GdeRjL GdJShjbjs